Les dêpots «areno-pelitiques» du littoral Nord du Portugal.· approche micromorpholo gique; implications paleopedologiques et paleoclimatiques - Texier, J. P.; Meireles, J. (Trabalhos de Antropologia e Etnologia, 2020)
The authors submit a new interpretation of «areno-pelitiques>> deposits of the northern littoral of Portugal. This proposal is based on micromorphological analysis of two representative sequences and on a former geological regional study. The «areno-pelitiques» deposits include atlantic ranker soils, in situ or reworked by colluvial phenomenons, and paleolagoonal formations. They imply a climate oscillating sometimes towards a temperate pole (edification of humus soils and lagoonal sedimentation), sometimes towards a more arid and colder pole (deposition of colluvium). From chronological data, they seem to be dated of the end of the last Interglacial, of the beginning of Würm, of Late glacial and of Holocene. It Thus exists an important hiatus the exact causes of which have to be elucided.